A statistical model suitable for describing weather persistence - SRINIVASAN, T. R. (MAUSAM, 1959)
Persistence is a factor of major importance in meteorological studies. In a system where there is no persistence, the probability p of occurrence of an event and q (=-1—p) that of non-occurrence are independent of what has happened previously. It can be easily seen that the cumulative frequencies Fs of occurrences of runs of length n or more are terms of the geometric series F, pF, p2F so that the ratio of the successive terms of the actual cumulative frequency distribution provides an estimate of the probability p. However, in persistent series such as are usually met with in meteorology the ratios of the cumulative figures are not constant and this feature which is brought about due to the effect of persistence requires to formulate a different model.